Camel milk inhibits murine hepatic carcinogenesis, initiated by diethylnitrosamine and promoted by phenobarbitone - Hala M.F. El Miniawy; Kawkab A. Ahmed; Mohamed A. Tony; Sameeh A. Mansour; Marwa M. Salah Khattab (International Journal of Veterinary Science and Medicine, 2014)
This study was carried out in order to investigate the possible inhibitory effect of camel milk (CM) on induced hepatocarcinogenesis in rats. Twenty-eight male rats were assigned into 4 groups (7 rats per group). Group I served as control negative. Group II treated with camel milk. Group III was injected I/P with diethylnitrosamine (DENA) (200 mg/kg) as a single dose and after one week received 500 ppm phenobarbitone in drinking water. Group IV injected with DENA as group III and treated with camel milk. Estimation of AST, ALT, albumin, total protein and alpha fetoprotein (AFP) in the serum of euthanized rats was performed. Histopathological examination and immunohistochemical staining of AFP and placental glutathione s transferase of the liver were carried out. Biochemical result at 38th week revealed an increase in serum AFP and a decrease in serum albumin on group III although no significance was detected. Histopathologically, the size of altered hepatic foci was smaller in the milk treated group (group IV). The number of mitotic figures observed in group IV was lower than group III. Hepatocellular carcinoma developed only in group III but not group IV. Immunohistochemical staining of AFP demonstrated an intense positive staining in group III and a weak positive staining in group IV. Similarly, the area percent of preneoplastic P-GST positive foci in liver was higher in group III than group IV. In conclusion, camel milk halted the progression of hepatocellular carcinoma.